Amylopectin starch granule lamellar structure as deduced from unit chain length data. (November 2020) - Zhong, Yuyue; Bertoft, Eric; Li, Zhihang; Blennow, Andreas; Liu, Xingxun
Abstract: In this study, the molecular and aggregation structures of nine types of pure amylopectin (waxy) starches from sorghum (WSS), wheat (WWS) and millet (WMS) were combinedly studied by Gel-Permeation Chromatography (GPC), Fluorophore-Assisted Carbohydrate Electrophoresis (FACE), Wide Angle X-ray Scattering (WAXS), and Small Angle X-ray Scattering (SAXS). The chain lengths (CL) and contents of amylopectin chain fractions were mainly related to the genotype. Pearson correlation analysis suggests that short amylopectin chains 1 (S1 chains, DP 6–18) were the main contributors to crystalline lamella; longer S1 chains resulted in decreased thickness ( d c ) of the crystalline lamellae. However, also the lengths of the short amylopectin chains 2 (S2, DP 19–30) related to d c showing a positive correlation. Therefore, WWS samples, with the highest average CL of the S2 chains and lowest CL of S1 chains, displayed the thickest crystalline lamellae and longest long period distance i.e. the sum of the crystalline and amorphous lamellar thickness, d ac . Among the different starches, WMS exhibited the thinnest crystalline lamellae and shortest d ac, and consequently had the second-highest CL of S1 chains and lowest CL of S2 chains of the samples. The d c and d ac of WSS were intermediate and related to its medium length of S1 chains and S2 chains. Our study provides information of structural parameters of different types of amylopectin starches and specifically provides evidence of the importance of S2 chains on the lamellar structure. Importantly, our data demonstrate that the total CLD of amylopectin can reflect internal CL of importance for starch granule lamellar features. Graphical abstract: Image 1 Highlights: Amylopectin total CLD reflects internal CL of importance for starch granule lamella. Short amylopectin chains of DP 6–18 (S1), in crystalline lamellae, made these thinner. Short amylopectin chains of DP 19–30 (S2), in crystalline lamellae, made these thicker. Waxy wheat starch had thickest crystalline lamellae, longest S2 chains and shortest S1.